Beyond Classroom Learning: Institutionalizing Mental Revolution Values in Indonesian State Islamic Senior High Schools - Warul Walidin; Imran Imran; Darwani Darwani; Sulaiman Sulaiman (Jurnal Ilmiah Peuradeun, 2026)
State Islamic Senior High Schools (Madrasah Aliyah Negeri/MAN) play a strategic role in strengthening students’ character and ethical development in Indonesia. This study investigates the strategies used to internalize mental revolution values in learning at four MAN in Indonesia: MAN 3 Jakarta, MAN 1 Kulon Progo Yogyakarta, MAN 1 Banda Aceh, and MAN 4 Aceh Besar. Employing a qualitative approach within a postpositivist paradigm, data were collected through in-depth interviews, participant observation, and documentation involving four principals and twenty teachers. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, coding, data display, and interpretation. The findings reveal six interrelated strategies for implementing mental revolution values: integrating values into classroom learning, developing a conducive madrasah culture, applying student-centered learning, using cooperative learning models, strengthening teacher exemplarity, and organizing self-development activities. The implementation focused on three core values—integrity, work ethic, and mutual cooperation—which contributed to strengthening students’ discipline, responsibility, creativity, optimism, and social solidarity. This study offers a multidimensional framework for institutionalizing national values within Islamic education and provides a relevant model for global discussions on value-based education and moral citizenship.